The Contractile Effects of Oxytocin, Ergonovine, and Carboprost and Their Combinations: An In Vitro Study on Human Myometrial Strips. Issue 1 (March 2016) - Balki, M.; Erik-Soussi, M.; Ramachandran, N.; Kingdom, J.; Carvalho, J.C.A.
Abstract : ( Anesth Analg. 2015;120:1074–1084) Uterine atony is the leading cause of postpartum hemorrhage (PPH) worldwide, and is responsible for 35% of maternal mortality. Oxytocin is currently the most commonly used drug for uterotonic therapy. Other drugs, such as ergonovine and carboprost can also be used when oxytocin has failed to improve uterine tone. The authors of this study compared the ability of both high and low doses of oxytocin versus ergonovine or carboprost, to contract myometrial muscle obtained from women undergoing cesarean delivery. They also investigated the effect that oxytocin pretreatment had on the contractile effect.